HANKOICHNUS ICHNOGEN. NOV., A NEW ARTHROPOD (?) TRACE FOSSIL FROM THE CARBONIFEROUS OF THE DONETS BASIN (UKRAINE) - Дернов, В.С. (Institute of Geological Sciences, NAS of Ukraine, 2023)
The flyschoid sediments of the Dyakove Group (Serpukhovian–Bashkirian) are exposed in the central part of the Donets Basin (Luhansk and Donetsk regions of Ukraine and Rostov Region of Russia). These sediments are important for studying the history of geological development of the Dnipro-Donets Downwarp. In addition, the sediments of the Dyakove Group contain deposits of a number of mineral resources (gold, ores of silver, lead, zinc, etc.). Nevertheless, the paleontological features of the Dyakove Group are poorly understood. This paper describes the phyllocarid (?) resting trace Hankoichnus bandersnatchi ichnogen and ichnosp. nov. from the early Bashkirian part of the Dyakove Group. Trace fossils of phyllocarids are poorly studied. Diagnosis of a new ichnogenus: a small phyllocarid (?) resting trace (Cubichnia), represented by a hexagon bounded on both sides by ridges (in fact, by grooves, since the described material is a convex hyporelief on the lower surface of a shale slab), with one small tubercle at one end. The ichnogenus Hankoichnus differs significantly from other resting traces of arthropods (e.g., Alph, Arborichnus, Kingella, Rusophycus, Selenichnites, Tonganoxichnus, etc.). The new ichnogenus has the greatest similarity with the trace fossils Gluckstadtella Savage, 1971. The difference between Hankoichnus and Gluckstadtella consists in the absence of imprints of producer’s limbs in Hankoichnus. The most likely makers of traces Hankoichnus are phyllocarid crustaceans. This is confirmed by the morphology of the trace and the remains of the carapace valves of these crustaceans, found together with Hankoichnus in the black shales in the complete absence of remains of other biota. Phyllocarid remains are relatively common in Devonian and Carboniferous black shales formed in a dysaerobic marine environment.